2003
DOI: 10.1063/1.1579843
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low-frequency noise in molecular beam epitaxy-grown GaN epilayers deposited on double buffer layers

Abstract: We report the growth of high-mobility Si-doped GaN epilayers utilizing unique double buffer layer ͑DBL͒ structures, which consist of a thin buffer layer and a thick GaN intermediate-temperature buffer layer ͑ITBL͒. In this study, three types of DBL were investigated: ͑i͒ thin GaN low-temperature buffer layer /GaN ITBL ͑type I͒; ͑ii͒ nitridated Ga metal film/GaN ITBL ͑type II͒; and ͑iii͒ thin AlN high-temperature buffer layer /GaN ITBL ͑type III͒. Systematic measurements were conducted on the electron mobilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Low-frequency noise measurement is a nondestructive characterization technique performed directly on the complete device structure. It has been shown that the low-frequency noise in a semiconductor device arises from the modulation of the device conductance due to the random capture and emission of carriers by localized states in the device. Under a constant voltage bias, the current fluctuation due to a single trap gives rise to a random telegraph noise with a power spectral density in the form of a Lorentzian, . Since the individual trapping and detrapping events are statistically independent, the total current noise power spectral density, S I ( f ), of the complete device is given by in which Δ I 0 is the current fluctuation arising from capture of a single carrier under constant voltage bias.…”
Section: Resultsmentioning
confidence: 99%
“…Low-frequency noise measurement is a nondestructive characterization technique performed directly on the complete device structure. It has been shown that the low-frequency noise in a semiconductor device arises from the modulation of the device conductance due to the random capture and emission of carriers by localized states in the device. Under a constant voltage bias, the current fluctuation due to a single trap gives rise to a random telegraph noise with a power spectral density in the form of a Lorentzian, . Since the individual trapping and detrapping events are statistically independent, the total current noise power spectral density, S I ( f ), of the complete device is given by in which Δ I 0 is the current fluctuation arising from capture of a single carrier under constant voltage bias.…”
Section: Resultsmentioning
confidence: 99%
“…Before transfer the stream, we store the stream data, in case of network fault and realize double buffering to make the data transfer better [8]. In Windows, the double buffer is widely used.…”
Section: B Generating the Network Streammentioning
confidence: 99%